Notch and Hippo signaling converge on Strawberry Notch 1 (Sbno1) to synergistically activate Cdx2 during specification of the trophectoderm - Watanabe, Yusuke (Sci Rep, 2017)
The first binary cell fate decision occurs at the morula stage and gives rise to two distinct types of cells that constitute the trophectoderm (TE) and inner cell mass (ICM). The cell fate determinant, Cdx2, is induced in TE cells and plays an essential role in their differentiation and maintenance. Notch and Hippo signaling cascades are assumed to converge onto regulatory elements of Cdx2, however, the underlying molecular mechanisms are largely unknown. Here, we show involvement of Strawberry Notch1 (Sbno1), a novel chromatin factor of the helicase superfamily 2, during preimplantation development. Sbno1 knockout embryos die at the preimplantation stage without forming a blastocoel, and Cdx2 is not turned on even though both Yap and Tead4 reside normally in nuclei. Accordingly, Sbno1 acts on the trophectoderm-enhancer (TEE) of Cdx2, ensuring its robust and synergistic activation by the Yap/Tead4 and NICD/Rbpj complexes. Interestingly, this synergism is enhanced when cells are mechanically stretched, which might reflect that TE cells are continuously stretched by the expanding ICM and blastocoel cavity. In addition, the histone chaperone, FACT (FAcilitates Chromatin Transcription) physically interacts with Sbno1. Our data provide new evidence on TE specification, highlighting unexpected but essential functions of the highly conserved chromatin factor, Sbno1.